2019
DOI: 10.1097/corr.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Symptomatic Venous Thromboembolism After Surgery for Spine Metastatic Bone Lesions: A Retrospective Study

Abstract: Background Cancer and spinal surgery are both considered risk factors for venous thromboembolism (VTE). However, the risk of symptomatic VTE for patients undergoing surgery for spine metastases remains undefined. Questions/purposes The purposes of this study were to: (1) identify the proportion of patients who develop symptomatic VTE within 90-days of surgical treatment for spine metastases; (2) identify the factors associated with the development of symptomatic VTE among patients receiving surgery for spine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 49 publications
2
40
1
Order By: Relevance
“…Therefore, it is reasonable to believe that this patient population has a higher prevalence of VTE. A recent retrospective study showed that 11% of patients with spinal metastases undergoing spinal surgery were observed to have symptomatic VTE ( 5 ). Accurately identifying risk factors related to VTE can help clinicians and patients determine which high-risk groups can be treated with interventions as soon as possible, which is very helpful for reducing perioperative mortality and improving postoperative survival time and quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is reasonable to believe that this patient population has a higher prevalence of VTE. A recent retrospective study showed that 11% of patients with spinal metastases undergoing spinal surgery were observed to have symptomatic VTE ( 5 ). Accurately identifying risk factors related to VTE can help clinicians and patients determine which high-risk groups can be treated with interventions as soon as possible, which is very helpful for reducing perioperative mortality and improving postoperative survival time and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…For the risk factors of VTE after spinal surgery, some studies have reported the corresponding results, and some risk scores have been established ( 6 8 ). However, it is still unclear whether these conclusions are equally applicable to spinal metastasis surgery, because the treatment measures and prognostic characteristics of patients with spinal metastases are very specific ( 5 ). Therefore, it is very necessary to identify the risk factors of VTE in patients with spinal metastases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, creating a cohort of patients' multiple bone metastases can propel research in understanding the impact of skeletal related events in this complicated patient population. In addition, the clinical feature 'single versus multiple bone metastases' can be used in various studies as a risk factor for an outcome, as was the case for the studies that supplied the bone-scintigraphy reports [13,14]. This could substantially reduce reviewer burden and error rate.…”
Section: Discussionmentioning
confidence: 99%
“…EHRs of patients in our institutional database of metastatic bone tumor were reviewed [13,14]. We identified 1780 potentially eligible patients after screening the medical records, of which 1076 patients did not have a preoperative bone scintigraphy within 6 months.…”
Section: Study Populationmentioning
confidence: 99%
“…Venous thromboembolism (VTE), which includes both deep vein thrombosis (DVT) and pulmonary embolism (PE), is one of the most-common and concerning complications these patients experience. Many thromboprophylaxis regimens are used in an attempt to minimize VTE, as seen by the highly varied regimens used in the current study by Groot and colleagues [3]. Despite aggressive perioperative thromboprophylaxis, the risk for postoperative VTE is prolonged well past the perioperative hospital stay [10].…”
mentioning
confidence: 89%